Penerapan Putusan Serta Merta (Uit Voerbaar Bij Voorraad) Terhadap Perkara Perdata Pada Pengadilan Negeri Pekanbaru Kelas I A. - Geremy Joy N; Mardalena Hanifah; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The judge's decision aims to resolve a dispute, the litigants have the option to submit anapplication for an immediate decision (Uitvoerbaar Bij Voorraadd) and efforts to make ithappen are regulated in Article 180 paragraph (1) HIR/Article 191 paragraph (1) Rbg,even though the Pekanbaru District Court Class I A often accepts requests for judgmentsimmediately (Uitvoerbaar Bij Voorraadd), but very rarely grants them. Immediateapplication of decisions (uit voerbaar bij voorraad) in civil cases in Register Number:26/Pdt.G/2012/PN.PBR and civil cases register number: 116/Pdt.G/2013/PN.PBR at thePekanbaru District Court Class 1A.This type of research can be classified into the type of sociological research, with theresearch location taking place at the Pekanbaru District Court Class IA, while thepopulation and sample are all parties related to the problem under study. This study usesdata sources in the form of primary data and secondary data, and data collectiontechniques are carried out by interviews.From the results of the study, there are two main things that can be concluded, firstly theapplication of an immediate decision (Uitvoerbaar Bij Voorraad) at the PekanbaruDistrict Court has clearly been effective and relevant to be guided by developments in theworld of justice, because before deciding an immediate decision, every condition has beenfulfilled in accordance provisions of the Supreme Court Circular Letter Number 3 of 2000Concerning Immediate Decisions (Uitvoerbaar Bij Voorraad) and Provisional andSupreme Court Circular Letter Number 4 of 2001 concerning Issues of ImmediateDecisions (Uitvoerbaar Bij Voorraad) and Provisionil. Decisions can immediatelybecome guidelines for judges to settle cases that cannot be executed because they do notinclude a commendator's order in their decision. Second, the obstacle to the granting ofan immediate decision (Uitvoerbaar Bij Voorraad) according to the materialrequirements lies in the discrepancy between the case and the facts of the trial, becausemany cases that ask for an immediate decision (Uitvoerbaar Bij Voorraad) tend not tomeet the requirements set by SEMA, because most cases are in court Pekanbaru State, didnot prepare the conditions needed to grant the decision immediately (Uitvoerbaar BijVoorraad). Formal obstacles when one of the seven requirements is met, the judge isinstructed not to decide the case immediately, but first to consult the chairman of the highcourt and the chairman of the district court, although this procedure tends to limit theindependence of judges, this is in accordance with the principle of prudence alwaysemphasized by the Supreme Court of the Republic of Indonesia in handling cases forwhich an immediate decision is requested (Uitvoerbaar Bij Voorraad).Keyword : Dispute, Civil Case, Implementation of Immidiate Verdict.